The Role of Universities in Protecting Intellectual Property of SMEs - Disemadi, Hari Sutra; Sudirman, Lu; Udu, Jericho (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to analyze the legal certainty in the protection of intellectual property for Small and Medium-sized Enterprises (SMEs) and to explore the role of higher education institutions in enhancing the effectiveness of intellectual property protection for SMEs. The absence of prior research specifically examining the relationship between these two aspects underscores the novelty of this research within the context of normative law. The research methodology employed is the normative legal research method, relying on the analysis of secondary data involving legal interpretation. The research findings indicate that the intellectual property regulations in Indonesia have provided a fundamental legal certainty for SME actors in their efforts to safeguard creativity and innovation. Higher education institutions, through community engagement activities, play a role in shaping a stronger 'legal culture' to enhance the effectiveness of intellectual property protection for SMEs. Higher education institutions can assist in improving the understanding of SME actors regarding the importance of registration and intellectual property protection.